Formal analysis of anxiety in cognitive model of interviewee mental state - Ajoge, Naseer Sanni; Ab. Aziz, Azizi; Mohd Yusof, Shahrul Azmi (2017)
Purpose - Anxiety is an aversive motivational state that occurs on a condition of perceived threat and its contributes to the definition of the mental state of an interviewee during interview session.In order to design an intelligent software agent that understands the states of an interviewee for the purpose of providing support, the various constructs that contribute to the formation of the interviewee mental state needs to be conceptualized and formally analysed.The construct of interview anxiety is the feeling of apprehension or anxiousness that is relatively paversive among applicants or contestants across interview events (McCarthy & Goffin, 2004). Interview involves social dialogue with unknown personality (interviewer) and talking with strangers in a situation where one has relatively low control trigers anxiety (Ayres, Keereetaweep, Chen, & Edwards, 1998).Therefore, anxiety can be considered as a fundamental factor in selection interview, since the process is highly evaluative and demanding in nature (R. Heimberg & Keller, 1986).Several programs have been designed to treat social anxiety and nonassertive behaviors from a cognitivebehavioral perspective (e.g., R. G. Heimberg, Madsen, Montgomery, & Mcnabb, 1980), however, programs for the cognitive-behavioral treatment of interview anxiety is not very popular.This perspective can be extended in the cognitive agent paradimn for designing intelligent artefact that provides supports for interviewee. Inteligent interview coaching systems have been built but mostly in recorgnising users based on verbal and non-verbal gestures that are measurable during interviews, e.g. MACH (Hoque, Matthieu, & Martin, 2013); and TARDIS (Anderson et al., 2013). In order to build a system capable to understand the mental state of the interviewee before providing the required support during interview sessions, the interplaying constructs that define such behaviours must be incoporated. The three major constructs that have been hypothesised to immensly interact to define the mental state of an interviewee are anxiety, self-efficacy and motivation (Huffcutt, Van Iddekinge, & Roth, 2011).This paper is on a formal model of interviewee anxiety which has been simulated and validated mathematically to determine possible equilibria points which serve to define the stability of the model.The validated model when fully integrated with models of interviewee self-efficacy and motivation constructs can serve as the basis for designing an intelligent agent that is capable of providing supportive interview coaching.